Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Kinerja Karyawan Pada PT. Perkebunan Nusantara IV Medan - Hendra Setiawan; Juliana Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Due to the industrial world's more strict advancement in the modern day, issues frequently arise that lead to a company's demise. In order to solve these issues, human resources must play a significant role. Effective workers can contribute to an organization's desired accomplishments. The most crucial component of a company that falls short of its objectives is its human resources. Article 1 of the 1969 Law concerning Basic Provisions Concerning Labor states that workers are defined as those who perform tasks and submit the results to their employers when the tasks are completed in a way that aligns with their job or profession based on their expertise as an eye. Of course, elements that affect an employee's performance, whether directly or indirectly, decide whether they perform well or poorly.